(3QSGdI aj JMQje GdPcQ LgQkG Ch GdQbU hGdSeGYs - (3eMeO Hf eQGO GdGQefcj,J (B950 (3g` s
(3ChdgG (B:s
(3bGd ai Yjhf GdJaGSjQ ai bhdg hGPcQ QHc ai faSc s
(3BNQgG (B:s
(3bhd GdfHi Udi Gddg Ydjg hSde GdTjWGf bGFe Ydi bGdH GHf BOe aEPG PcQ Gddg NfS hEPG Ybd hShS JeJ GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdChds
(3fSNI KGfjI ef GdeNWhW Qbe (B" 186 " (3JUhas
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdbQGAGJ hGdJLhjOs